1994
DOI: 10.1046/j.1525-1438.1994.04020094.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear morphometry and DNA flow cytometry as prognostic methods for endometrial carcinoma

Abstract: In a series of 227 women with endometrial carcinoma stages I-IV the prognostic value of nuclear morphometry and DNA analysis was evaluated prospectively. The tumors were also classified according to histologic subtype, degree of differentiation (FIGO), and nuclear grade. The DNA analysis (ploidy and S-phase fraction) was made using flow cytometry on fresh-frozen tissue. The morphometric measurements and the grading of the tumors were done on both fresh-frozen tissue and on formalin-fixed and paraffin-embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 3 publications
3
23
0
Order By: Relevance
“…Van der Putten et al 27 reported an independent prognostic impact of nuclear morphometry in a small series of Stage I endometrial carcinoma patients. In a larger study examining only curettage specimens due to preoperative radiation therapy, a prognostic impact of nuclear morphometry was reported by Sorbe et al 28 Our current results are in accordance with previous findings, although nuclear perimeter was found to be prognostically the most powerful in our series compared with DMIN in the earlier reports. 27,28 However, all variables expressing nuclear size had a prognostic impact in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Van der Putten et al 27 reported an independent prognostic impact of nuclear morphometry in a small series of Stage I endometrial carcinoma patients. In a larger study examining only curettage specimens due to preoperative radiation therapy, a prognostic impact of nuclear morphometry was reported by Sorbe et al 28 Our current results are in accordance with previous findings, although nuclear perimeter was found to be prognostically the most powerful in our series compared with DMIN in the earlier reports. 27,28 However, all variables expressing nuclear size had a prognostic impact in our study.…”
Section: Discussionsupporting
confidence: 93%
“…6). Sorbe et al (22) also found that myometrial invasion DNA-ploidy, %S-phase cells and the mean shortest nuclear axis, were prognostically the most significant, thus confirming the value of the essential features of the ECPI-1. Abeler et al (23) found that the prognostic value of vascular invasion was limited.…”
Section: Discussionmentioning
confidence: 82%
“…This finding is well supported in the literature [39,40,50,52,64] . The presence of this atypical DNA suggests a prognosis that is poorer than a sample with normal DNA [6,8,11,13,14,16,24,39,41,43,52,59,60,66,70] . The aneuploid characterization of these benign tumors should at least require a closer, independent pathological examination.…”
Section: Resultsmentioning
confidence: 98%
“…Papers that do not publish their coefficients of variation and do not show representative DNA histograms should be reviewed with caution [39,40,[43][44][45][46] . Furthermore, preparation techniques using formalin-fixed, paraffinated tissues that use a low pH of 2.0 and non-DNA specific staining methods, such as propidium iodide, are less than ideal in performing the proper sample preparation [47] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation